Human mucocutaneous leishmaniasis in Três Braços, Bahia - Brazil: an area of Leishmania braziliensis braziliensis transmission. II. Cutaneous disease. Presentation and evolution - Elmer A. Llanos-Cuentas; Philip D. Marsden; Edinaldo L. Lago; Air C. Barreto; César C. Cuba; Warren D. Johnson (Revista da Sociedade Brasileira de Medicina Tropical, 1984)
The clinical records of 182 patients with cutaneous leishmaniasis probably due to Leishmania braziliensis braziliensis are analysed. 68% had a single lesion which was usually an ulceron the lower anterior tibial third. Many had short histories of one to two months and all age groups were represented 13% had closed lesions of a verrucose or plaque like nature. Evolution of these skin lesions after treatment was related to the regularity of antimony therapy. Although healing usually occurred in three months, the time to scarring after commencing treatment was variable and related to the size ofthe lesion (p < 0.01). Usually if sufficient antimony treatment was given the lesion closed. Seven of the ten patients with initially negative leishmanin skin tests converted to positive after treatment. A significant decline of indirect fluorescent antibody titres occurred in patients followed, during and after therapy.